IMPLEMENTASI PENGEMBANGAN KECERDASAN SPIRITUAL ANAK MELALUI METODE PEMBIASAAN DI SD ISLAM PLUS MASYITHOH KROYA KABUPATEN CILACAP - Fita Tri Wijayanti (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2018)
This study aims to describe and analyze it critical about the implementation of the development of children's spiritual intelligence through habituation methods at SD Islam Plus Masyithoh Kroya, Cilacap district. This type of research is field research or field research. This research is presented in descriptive form with the aim to describe a process that occurs in the field. While the approach taken is a qualitative approach. Data collection techniques used: observation, interviews, and documentation. While the data analysis technique uses the Miles and Huberman Model, which consists of: Data Reduction, Data Display and Verification (Conclusion Drawing). The results of this study found that the forms of development of children's spiritual intelligence through habituation methods at SD Islam Plus Masyithoh Kroya were divided into two activities, namely: first, programmed habituation activities, including extracurricular activities scheduled every Saturday namely extracurricular tilawah, tambourine and calligraphy . In addition, outdoor learning, activities that have been scheduled each year for grade 5 (five) students, are religious tourism. Second, habituation activities are not programmed in the development of children's spiritual intelligence through habituation methods. a) routine activities, carried out continuously and scheduled. The routine activities include: morning munajat activities (asmaul husna, daily prayers, tartil juz 30, and memorizing selected hadith) which are carried out before teaching and learning activities, dhuha prayer, dzuhur prayer in congregation, and social service activities, b) spontaneous namely activities that occur when experiencing special events. In this case the spontaneous activities carried out included: greeting, apologizing before asking for help, always dhikr, and thanking, c) exemplary is a habituation activity shown by the teacher in daily actions. Exemplary here is shown by the performance of the teacher both in the classroom providing subject matter as well as outside the classroom.